Email Spam Classification Tool Using Artificial Neural Network (ANN) With Logistic Activation Function - Abdullah, Nurul Azma; Anthoni, Alvin Ericson; Palaniappan, P. Siva Shamala (Applied Information Technology And Computer Science, 2020)
Abstract: This project is all about developing a tool that has the ability to detect spam emails using Artificial Neural Network (ANN) with Logistic Activation Function. This project implements spam detection using artificial neural network which helps to detect whether an email is spam or ham. Artificial Neural Network (ANN) is an information processing paradigm that is inspired by the way biological nervous systems, such as the brain, process information. In artificial neural network, it helps to detect the input whether it is a spam or ham in this case to give the output with a range from 0 to 1. This project will be able to overcome the weaknesses and flaws in the existing tool or application by giving output which can be trusted and maintains confidentiality, integrity, and availability.